Five new synonyms in Serpocaulon (Polypodiaceae) - Sanín, David; Salino, Alexandre (Phytotaxa, 2018)
A new taxonomic circumscription is proposed for Serpocaulon sessilifolium and S. wagneri. We compared the type specimens of S. sessilifolium and S. wagneri with those of the new proposed synonyms: S. acuminatum, S. antillense and S. chacapoyense for the former, and Polypodium kuhlmannii and S. panorense for the latter. Diagnostic descriptions, synonymy, taxonomic discussion, and pictures of diagnostic characters for each species are provided. In addition, lectotypes for two names are designated.